1998
DOI: 10.1136/bjo.82.12.1424
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic barriers to cataract surgery in Nepal: the south Asian cataract management study

Abstract: It was found that in this population with a majority of patients with severe vision loss and blind, even when offered transport and free surgery the utilisation of cataract surgery is below 60%. Medicine tends to be prescriptive based on technological advances that it is able to offer. Medical practice needs to develop a more holistic understanding of the needs of the communities cultivating a greater capability to analyse the role of cultural, social, and economic factors when planning medical services for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 7 publications
7
98
1
1
Order By: Relevance
“…Similar findings have been reported among Nepalese patients with cataracts, of which a third reported fear as the main reason for not seeking surgical care. [13] This is in contrast to India, Myanmar and Nigeria where less than 15% of patients with cataracts reported fear as a barrier to surgical care. [26][27][28] However, similar findings from other LMICs demonstrate that this is not unique to Nepal.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Similar findings have been reported among Nepalese patients with cataracts, of which a third reported fear as the main reason for not seeking surgical care. [13] This is in contrast to India, Myanmar and Nigeria where less than 15% of patients with cataracts reported fear as a barrier to surgical care. [26][27][28] However, similar findings from other LMICs demonstrate that this is not unique to Nepal.…”
Section: Discussionmentioning
confidence: 56%
“…[6,10] Moreover, those in need of surgery face significant access to care barriers including: excessive distance to capable health facilities, poor roads, inability to afford care, fear and mistrust of the healthcare system. [11][12][13] Resultantly, many surgical conditions go untreated, increasing the risk of complications and emergency sequela of their disease. LMICs report significantly higher rates of incarceration, strangulation and death from hernias than high-income countries that have better access to essential surgical care.…”
Section: Introductionmentioning
confidence: 99%
“…21 In developing countries the uptake of cataract surgery, when freely available, can still be low because individuals fear surgery or do not have the time. 22 In Australia lack of knowledge about eye disease was very common, 23 particularly in those with lower levels of education and this could explain the reluctance of some to access eye health services. In the UK it has been suggested that the failure to integrate vision checks for the elderly into primary care, a reluctance to add to waiting lists and uncertainties about treatment and outcome may be to blame.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Nepal, 5 India, 6 and Nigeria 7 show that people are not aware of the benefits of cataract surgery. Cataract blindness is more common in poor, rural, and illiterate patients than in wealthy urban and educated individuals.…”
Section: Awarenessmentioning
confidence: 99%
“…5 The costs of surgery include not only the price of the operation, and the cost of transport to and from the clinic, but also lost income for the carer and the patient. Patients who are willing to attend for surgery may be unable to persuade relatives to accompany them.…”
Section: Costmentioning
confidence: 99%